2022
DOI: 10.1038/s41427-022-00402-7
|View full text |Cite
|
Sign up to set email alerts
|

Physically driven enhancement of the stability of Bi2O3-based ionic conductors via grain boundary engineering

Abstract: Fast oxygen-ion conductors for use as electrolyte materials have been sought for energy conversion and storage. Bi2O3-based ionic conductors that exhibit the highest known oxygen-ion conductivities have received attention for use in next-generation solid electrolytes. However, at intermediate temperatures below ~600 °C, their conductivities degrade rapidly owing to a cubic-to-rhombohedral phase transformation. Here, we demonstrate that physical manipulation of the grain structure can be used to preserve the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…This observation suggests the occurrence of chemical vapor deposition (CVD)-like growth, even in the absence of self-decomposition of the Bi precursor under these conditions. This observed behavior is likely attributable to the significant oxygen ion permeability of BiO x . , Such a characteristic enables the movement of oxygen ions within the thin film to the surface. There, the oxygen reacts with the Bi precursor, facilitating adsorption and subsequent deposition reactions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation suggests the occurrence of chemical vapor deposition (CVD)-like growth, even in the absence of self-decomposition of the Bi precursor under these conditions. This observed behavior is likely attributable to the significant oxygen ion permeability of BiO x . , Such a characteristic enables the movement of oxygen ions within the thin film to the surface. There, the oxygen reacts with the Bi precursor, facilitating adsorption and subsequent deposition reactions.…”
Section: Resultsmentioning
confidence: 99%
“…This observed behavior is likely attributable to the significant oxygen ion permeability of BiO x . 23,24 Such a characteristic enables the movement of oxygen ions within the thin film to the surface. There, the oxygen reacts with the Bi precursor, facilitating adsorption and subsequent deposition reactions.…”
Section: Resultsmentioning
confidence: 99%
“…[17] The doping strategy with high-valence cations (e.g., Nb 5+ and Ta 5+ ) has been suggested to stabilize the SrCoO 3-𝛿 (SCO) structure. [18,19,20] Du et al demonstrated that Sc-involved bimetal doping effectively enhances the ORR activity of SCO-based oxygen electrode in solid oxide electrochemical cells (SOCs). [21] Similarly, the incorporating Ta into BCO transformed hexagonal perovskite into cubic perovskite, resulting in notable improvements in its electrochemical characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Alternative electrolytes having higher ionic conductivity than conventional stabilized zirconia have therefore become increasingly attractive for use in IT-SOFCs [2,3]. To date, most studies on electrolytes possessing satisfactory oxygen ion conductivity at decreased temperatures have been focused on oxide materials with cubic fluorite structures, such as doped CeO 2 [4,5] and Bi 2 O 3 [6,7]. Nevertheless, despite high ionic conductivity, which is very attractive for designing IT-SOFCs, these electrolytes, along with having advantages over traditional electrolytes based on zirconium dioxide, have a number of disadvantages.…”
Section: Introductionmentioning
confidence: 99%